2016
DOI: 10.1007/978-3-319-40244-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Body Motion Analysis for Emotion Recognition in Serious Games

Abstract: In this paper, we present an emotion recognition methodology that utilizes information extracted from body motion analysis to assess affective state during gameplay scenarios. A set of kinematic and geometrical features are extracted from joint-oriented skeleton tracking and are fed to a deep learning network classifier. In order to evaluate the performance of our methodology, we created a dataset with Microsoft Kinect recordings of body motions expressing the five basic emotions (anger, happiness, fear, sadne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The majority of state of the art emotion recognition frameworks capitalize mainly on facial expression or voice analysis, however, research in the field of experimental and developmental psychology has shown that body movements, body postures, or the quantity or quality of movement behavior in general, can also be of help to differentiate between emotions [57]. To this end, we decided to extract a number of 3D body features, which are deeply inspired by the relevant psychological literature [56] [58].…”
Section: B Body Motion Analysis For Emotion Recognitionmentioning
confidence: 99%
“…The majority of state of the art emotion recognition frameworks capitalize mainly on facial expression or voice analysis, however, research in the field of experimental and developmental psychology has shown that body movements, body postures, or the quantity or quality of movement behavior in general, can also be of help to differentiate between emotions [57]. To this end, we decided to extract a number of 3D body features, which are deeply inspired by the relevant psychological literature [56] [58].…”
Section: B Body Motion Analysis For Emotion Recognitionmentioning
confidence: 99%
“…In order to compare the proposed method with other classification methods, we calculated the most commonly used features, such as kinematic related features (velocity, acceleration, kinetic energy), spatial extent related features (bounding box volume, contraction index, density), smoothness related features, leaning related features and distance related features. During features extraction we strictly followed approach presented in Reference [ 23 ], since the authors obtained very promising results on a database derived from Kinect recordings. We juxtaposed several well known classification methods to verify the above-mentioned features and their effectiveness in gestures-based emotion recognition.…”
Section: Resultsmentioning
confidence: 99%
“…However, it must be emphasised that the superior performance is associated with the type of analysed data. In Reference [ 23 ] emotions are represented as predetermined gestures (each emotion is assigned to particular type of gesture, for example, power pose to happiness). The actors/actresses are instructed how to present particular emotional state prior to recording.…”
Section: Introductionmentioning
confidence: 99%
“…A series of multimodal observation channels are established from input sensors connected to player devices including microphones, cameras and keyboard, in addition to more advanced gaming sensors such as Microsoft Kinect and Leap Motion. Using sensing and classification techniques emotion from voice, facial expression and body language is acquired and then fusion processes applied to provide the emotional state of the user [5][6].…”
Section: Interaction With Sensorsmentioning
confidence: 99%